Pengaruh Motivasi, Budaya Organisasi, dan Lingkungan Kerja terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Mediasi (Kajian Studi Literatur Manajemen Sumber Daya Manusia) - Daryanto, Fhifie; E.H.J. FoEh, John; Sia Niha, Simon (Green Publisher, 2023)
This study is aimed at finding out whether the influence of motivation, organizational culture, and work environment can influence employee performance through job satisfaction as a mediating variable. In improving the quality and productivity of the workforce, it is important for organizations to have an understanding of the aspects that can have an impact on the performance of their employees. Motivation is seen as a trigger for individual behavior and is a key factor that encourages individuals to act or carry out activities. Organizational culture is a factor that differentiates one organization from another, and the main characteristics in organizational culture are highly valued by each member. The work environment plays an important role in creating comfortable and supportive conditions for workers. An adequate work environment can form harmonious working relationships between employees. Job satisfaction is reflected in the general view a person has of his or her job. This literature review involves a review of articles, scientific journals, and related research that has been conducted previously. The results of this literature review will later be used to determine the relationship between variables in previous research, and will become the basis for further thesis research.